The One-Pot Three Components of Iodone, Schiff Base and Epoxide for Synthesis Iodohydrins (Global Journal of Science Frontier Research, 2012)
In study we report synthesis Iodohydrines in absence of the complexes Schiff-base Salen Cu, Ni and Co.The experimental results showed both that the catalysts had higher catalytic activity and better epoxide selectivity than the homogeneous catalyst.
Keywords: Schiff base; Iodohydrin; ligand; iodine; homogeneous